Pandangan Masyarakat Desa Sigala-Gala terhadap Pemilihan Imam Tetap Masjid Menurut Hukum Islam - Mahmudin Hasibuan; Laila Izza; Winun Arwiyah; Khoirul Ilham; Panaekan Hasibuan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the concept of permanent imam at the Sigala-gala Village Mosque in the perspective of Islamic law. The research subjects consisted of the people of Sigala-gala Village who live as many as four people, the village head, the customary leader, and the mosque imam. The object of research is the concept of determining a permanent imam in the mosque. The research method used is qualitative with data collection techniques through observation, interviews. Data analysis is carried out with data reduction steps, data presentation, and conclusion drawing. To ensure data validity, credibility, transferability, dependability, and confirmability tests were used. The results showed that the concept of permanent priests in the Sigala-gala Village Mosque was not fully in accordance with the provisions of Islamic law. The determination of the imam is mostly based on the quality of recitation and a beautiful voice, without paying attention to the overall requirements set out in Islamic law, such as a deep understanding of prayer procedures, justice, and good character. In the perspective of Islamic law, the prayer imam must fulfill certain conditions, including being Muslim, puberty, male, fluent in reading the Qur'an, understanding the correct prayer procedures, no shar'i excuse, knowledgeable, fair, and good character. A comparison between the provisions of the Shari'ah and the existing practices in Sigala-gala Village shows a gap, so that improvements are needed in the determination of permanent imams to be in accordance with the guidance of Islamic law.